Wash only a bookkeeper : a biography of Washingon Z. SyCip - Dalisay, Jose Y., Jr. (Makati City, Philippines : SGV Foundation and the AIM Scientific Research Foundation, 2021)
A biography of Washington Z. SyCip, who was born in Manila in 1921. He went on to become one of the foremost practitioners of accounting in the Philippines and Asia, as well as a prime advocate of closer cooperation between the United States, Europe, and Asia.
Part One. Passenger on a Ship -- Part Two. To Stay and to serve -- Part three. Building Up the Firm -- Part four. Family and Friends -- Part Five. The Asian dream -- Part Six Beyond Retirement -- Postscript. The SyCip Legacy -- A Good Night's Sleep -- Appendix -- Index.
Includes index.
Keywords: ACCOUNTANTS -- PHILIPPINES -- BIOGRAPHY